PEMANFAATAN WAKTU LUANG PESERTA DIDIK PADA JAM SEKOLAH DI KELAS TINGGI SD NEGERI 1 JEUMPET KABUPATEN ACEH BESAR - Dila Syafira Ramadhini; Darnius Said; Aida Fitri (Universitas Syiah Kuala, 2022)
The purpose of this study is to explain how the use of students' free time during school hours in the high class of SD Negeri 1 Jeumpet Aceh Besar. The research method used is qualitative and this research is descriptive. The subjects in the study were students in grades IV, V, and VI, totaling 60 people, and homeroom teachers for grades IV, V, VI. To obtain data, researchers used data collection techniques of observation, interviews and questionnaires (questionnaires). The data analysis technique was carried out with the data reduction stage, data display and drawing conclusions and using the percentage form. Based on the results of data analysis, it was found that students used their free time during school hours for various activities, namely sports activities including gymnastics, badminton, and football, artistic activities, namely making handicrafts from origami materials, and religious activities, including reading prayers, reading Surah Yasin. , memorize short surahs, read the Qur'an, and perform prayers. Based on the results of data analysis through questionnaires (questionnaires) from 60 students, 60% of respondents answered that they always use their free time during school hours to do sports activities, 35% of respondents answered that they always use their free time during school hours to do art activities, and 48% of respondents answered that he always used his free time during school hours to carry out religious activities. The activities that are most in demand by students are sports activities such as gymnastics, badminton, and football. So, it can be concluded that students of SDN 1 Jeupet Aceh Besar have used their free time for positive activities such as gymnastics, playing badminton and soccer, making handicrafts, reading prayers, reading the Qur'an, memorizing short suras, and performing prayers.